Design and construction of the sandwich-like Z-scheme multicomponent CdS/Ag/Bi2MoO6 heterostructure with enhanced photocatalytic performance in RhB photodegradation. (2nd September 2016) - Wang, Danjun; Shen, Huidong; Guo, Li; Fu, Feng; Liang, Yucang
Abstract : A rationally designed and successfully fabricated all-solid-state Z-scheme photocatalyst, CdS/Ag/Bi2 MoO6, with a sandwich-like multicomponent heterostructure, shows an enhanced photocatalytic performance in RhB degradation. Abstract : A sandwich-like Z-scheme tricomponent CdS/Ag/Bi2 MoO6 photocatalytic system was rationally designed and successfully fabricated, in which Ag was loaded onto Bi2 MoO6 microspheres by a facile photoreduction method and CdS was subsequently deposited onto the surface of Bi2 MoO6 and Ag/Bi2 MoO6 through a deposition–precipitation method. During this process, a series of Ag/Bi2 MoO6 and CdS/Bi2 MoO6 were also prepared. All the composites were characterized by XRD, TEM, SEM, EDX, XPS, UV-vis DRS, and IR spectra to confirm the successful integration of Ag or (and) CdS with Bi2 MoO6, the alteration of morphology and the formation of a new phase before and after Ag or (and) CdS loading. The degradation of rhodamine B (RhB) dye under visible light irradiation (>420 nm) revealed that the CdS/Ag/Bi2 MoO6 composite exhibited a highly visible-light-responsive photocatalytic performance compared to single Bi2 MoO6 or CdS and dual Ag/Bi2 MoO6 or CdS/Bi2 MoO6 . The enhanced photocatalytic performance of CdS/Ag/Bi2 MoO6 was ascribed to its special structure – a typical Z-scheme photocatalytic system, in which Ag nanoparticles directly connected to the surface of CdS and Bi2 MoO6 to form a solid–solid interface (ohmic contact), acting as a conductor that greatly shortened the distance for photogenerated electron transfer and combined photogenerated electrons from the CB of Bi2 MoO6 with the photogenerated holes from the VB of CdS through ohmic contact, and thereby led to the efficient separation of photogenerated electrons and holes and showed stable and strong reducibility and oxidizability. Moreover, the surface plasmon resonance effect of metallic Ag nanoparticles also played an important role in the enhanced photocatalytic performance of RhB degradation under visible light irradiation. Furthermore, investigations on photoluminescence and photoelectrochemical properties also demonstrated indirectly the highly efficient separation of photogenerated electrons and holes in the Z-scheme CdS/Ag/Bi2 MoO6 photocatalytic system. This new Z-scheme photocatalytic system will be applied to more photoreactions in further exploration.